SIFAT PEREKATAN KAYU MAHANG (Macaranga hypoleuca) ASAL HUTAN RAWA GAMBUT KABUPATEN PULANG PISAU (Wood Adhesion Properties of Macaranga hypoleuca from Peat-Swamp Forest in Pulang Pisau District): Yanciluk dan M. Damiri - Admin JHT (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2015)
ABSTRACTThis study was aimed to determine the wood adhesion properties of mahang (Macaranga hypoleuca) from Peat-Swamp Forest in Pulang Pisau District, as well as the influence of the axial and radial position of the adhesive properties of mahang wood and wood allotment of mahang for raw material wood processing industry. The research used the Factorial Complete Random Design (CRD) 3 x 2. The first factor was the actial wood position (A) consist of the bottom (A1), the middle (A2), and the top (A3). The second factor was radial position consist of axial (B1) and radial (B2). The data were analyzed using Honestly Significant Difference (HSD). Testing properties of solid wood sliding firmness and constancy gluing wood with ASTM procedure of D 905-49. Research result showed that properties of mahang wood adhesive as follow: firmness sliding radial cross-section namely 57.3 kg per cm2, firmness sliding sectional tangential namely 70.3 kg per cm2, bonding strength of the radial cross-section namely 58.7 kg per cm2, bonding strength tangential cross section namely 63.2 kg per cm2, percent damage to the radial cross-section namely 41.8% and tangential cross section namely 13.3%. There is a relationship of correspondence between adhesive properties and quality of the wood to influence the direction of the axial and radial position of mahang wood. Keywords: Adhesive properties, axial, radial, mahang